Structures of the Kalsilite-Like Silicates MTSiO4 (M = Ba, Na/K, Ca/Sr; T = Co, Mg, Zn, Ga, Be) - Liu, Bo (My University, 1992)
A number of silicate compounds BaTSiO4 (T = Co, Mg, Zn), Na0.5K0.5GaSiO4 and Sr1-xCaxBeSiO4 (x = 0.0 ~ 0.4) have been characterized by a combination of diffraction techniques. These compounds crystallize with the same (√3XA, C) superstructure of the hexagonal kalsilite (KAlSiO4) structure and belong to the large structural family of stuffed tridymite-derivatives. Their crystal structures have been refined by using powder neutron data (BaTSiO4, T = Mg, Zn), powder X-ray data (Na0.5K0.5 GaSiO4) and single crystal X-ray data (BaCoSiO4 and Sr1-xCaxBeSiO4, x = 0.0 and 0.27). This study shows that these kalsilite-like structures can accommodate cavity and tetrahedral atoms of variable sizes by relatively minor framework distortions and atomic displacements. The formation of the (√3XA, C) superstructure can be correlated with the relative sizes of the tetrahedral and cavity atoms.
Keywords: structures, silicates, compounds, diffraction, single, crystal, atoms